Reflections IX and X: Reflections from Education and the Arts in the COVID-19 Era - Freedman, Kerry; Escaño, Carlos (Communiars. Revista de Imagen, Artes y Educación Crítica y Social, 2020)
Reflection IX is a text developed by Kerry Freedman, Professor and researcher at Norhern Illinois University (USA). Dr Freedman is an international reference for contemporary art education and visual culture pedagogy. Carlos Escaño, Associate Professor of art education at the University of Seville with interests in digital culture and critical thinking, develops Reflection X, which enters into conversation with some of the issues proposed in Reflexion IX.